NANOTECHNOLOGY AND ITS INFLUENCE ON THE EVOLUTION OF MEDICINE - De Paula Silva, Thamily; Scombatti Pinto, Giuliano (Revista Interface Tecnológica, 2020)
The application of an emerging technology called nanotechnology has been strongly developed in several fields of human knowledge. The focus of this study is to highlight its use in partnership with one of these fields, medicine, demonstrating that technology and society always evolve in constant partnership. The present article was based on bibliographic research, proposing an understanding of the concept of nanotechnology, highlighting its origin, development, evolution process, and verifying that it is one of the great potentials for global investment. The study goes even deeper into which medical applications nanotechnology is currently present in and explores which ones it will do in the future. With that, it was noted that nanotechnology will be largely responsible for medical developments, due to its ability to provide benefits to the medical field, improving treatments, diagnoses, and surgeries. It is evident that to be applied to an environment, nanotechnology needs the help of structures and materials with nanometric dimensions, capable of reaching depths that no other biotechnological evolution has achieved before and with this, is capable of providing countless benefits to society.
Keywords: Nanotechnology; Medicine; Evolution; Technology; Benefits